Sharia Legal Certainty in Boycotts: Assessing the Implications of Fatwas on Socio-Economic Justice - Nadia; Arief, Ahmad; Turobovich, Juraev Abror (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aimed to examine the effectiveness of Fatwa No. 14/Ijtima' Ulama/VIII/2024 in clarifying the ambiguities of No. 83 of 2023, which addresses the boycott of products affiliated with Israel. The legal certainty provided by Fatwa No. 14, its role in guiding the public and businesses, and its broader socio-economic implications were evaluated. The study adopted content analysis, historiographical review, and documentary to analyze primary and secondary sources, such as official fatwas, policy reports, academic journals, and media reports. This method assesses the fatwa’s clarity, its social impact, and potential economic consequences. The result showed that Fatwa No. 14 aimed to resolve the ambiguity of No. 83 by promoting domestic products, local ownership, and national labor. However, the criteria remain imprecise, particularly concerning foreign ownership limits and the proportion of local raw materials, leading to public confusion and potential economic losses for unrelated businesses. Reactions to the fatwa have been polarized, with some perceiving the decree as a demonstration of economic solidarity, while others criticize the adverse effects of the fatwa on local businesses. This study provides a comprehensive legal and socio-economic assessment of MUI's fatwa on product boycotts, showing legal ambiguities and policy gaps that have yet to be addressed. By bridging Islamic legal studies and economic analysis, the study offers a novel perspective on the intersection of religious decrees and market dynamics. There is also a need for clearer guidelines and regulatory frameworks to ensure the fatwa’s effectiveness while minimizing unintended economic repercussions. In conclusion, this study contributes to the broader discourse on Sharia legal certainty, religious fatwas, and the impact on socio-economic justice.